2004
DOI: 10.1161/01.cir.0000148177.82319.c7
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Right-Left Heart Sequential Cardiac Resynchronization in Patients With Heart Failure, Chronic Atrial Fibrillation, and Atrioventricular Nodal Block

Abstract: Background-Single-site ventricular pacing in patients with heart failure, atrial fibrillation, and severe atrioventricular (AV) nodal block risks the generation of discoordinate contraction. Whether altering the site of stimulation can offset this detrimental effect and what role sequential right ventricular-left ventricular (RV-LV) stimulation might play in such patients remain unknown. Methods and Results-Nine subjects with heart failure (ejection fraction, 14% to 30%), atrial fibrillation, and AV block were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
73
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 31 publications
10
73
2
1
Order By: Relevance
“…The ectopic excitation of the RV apical area more expresses the inotropic effect on the pump function in both ventricles in dogs. At that, parameters of cardiac hemodynamics were significantly lower at pacing of the RV apex that corresponds to the data of other authors [6,[15][16][17][18][19][20]. In amphibians the indices of the pump function of the heart decreased at ventricular pacing (base and apex).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The ectopic excitation of the RV apical area more expresses the inotropic effect on the pump function in both ventricles in dogs. At that, parameters of cardiac hemodynamics were significantly lower at pacing of the RV apex that corresponds to the data of other authors [6,[15][16][17][18][19][20]. In amphibians the indices of the pump function of the heart decreased at ventricular pacing (base and apex).…”
Section: Discussionsupporting
confidence: 89%
“…Many studies report that only LV pacing leads to the increase of the duration of contraction and thus, reduces velocity of isovolumic relaxation of the ventricle [18,26]. In the present study we found out that ventricular pacing in dogs and amphibians decreases isovolumic indices (dP/dt max and dP/dt min ).…”
Section: Discussionsupporting
confidence: 59%
“…Hay et al reported the results of a comparison of the acute hemodynamic effects of BVP using RVA and RVOT/septal sites in 6 patients with AF and found no differences. 23 In their study, however, details of the septal sites were not clarified. We consider that the septal sites of the RV are important sites for BVP and clearly demonstrated in our study that the RV septal pacing site was important for better hemodynamic outcomes with BVP.…”
Section: Hemodynamic Assessment Of the Rvot And Rv Mid-septummentioning
confidence: 93%
“…[17][18][19][20] It is well known that aortic pulse pressure directly correlates with cardiac output at a constant heart rate and vascular load, 21 so most studies have examined pulse pressure as a measurement variable. However, a significant correlation between the changes in pulse pressure and clinical outcome was not found in those studies [17][18][19][20] and none have reported that a rise in SBP predicts the short-and long-term clinical outcome after CRT.…”
Section: Crt Predictors and Sbp Risementioning
confidence: 99%
“…19,[22][23][24] Molhoek et al studied patients with and without chronic AF and showed that their clinical parameters improved after 6 months of CRT and the rate of non-responders was greater among patients with AF. 22 Delnoy et al showed that the benefit of CRT in patients with chronic AF and HF was similar to that in patients with SR, and that long-term survival after CRT did not differ between the AF and SR groups.…”
Section: Comparison Of Response To Crt In Patients With Sr Vs Chronic Afmentioning
confidence: 99%